Leadership Influence and Work Environment on Employee Effectiveness in Capital Investment and Integrated Services in One Door City of Gorontalo - Aneta, Yanti; Turtono, Bondan (Asia Pacific Journal of Management and Education (APJME), 2019)
This study aims to determine the magnitude of the influence of leadership, and the work environment on the work effectiveness of employees in the Gorontalo City Investment and Integrated One-Stop Service. The research approach used is quantitative methods. Sources of data in this study are primary data that is carried out using questionnaires on respondents who have met the standards of the study sample. The data analysis technique used is multiple regression analysis using SPSS program assistance. The results of the study show that (1) Leadership has a positive but not significant effect on the effectiveness of employees in Gorontalo Investment and One-Stop Services in the City of Gorontalo. This is because based on the results of the descriptive analysis shows that the Leadership variable lies in the criteria that are "quite good". (2) The work environment has a positive and significant effect on the work effectiveness of employees in the Gorontalo City Investment and One Stop Service. Meanwhile, the results of the descriptive analysis show that the working environment variable lies in good criteria. (3) Leadership and workplace environment together have a positive and significant effect on the variable work effectiveness of employees in the Gorontalo City Investment and One Stop Service. The determination coefficient or R Square number is 0.493. This value shows that as much as 49.3% variability The work effectiveness of Gorontalo Capital Investment Service and Integrated One-Stop Service staff can be influenced by Leadership and Work Environment while the remaining 50.7% is influenced by other variables not examined in this study. The other variables are in the form of organizational culture variables, work discipline, compensation, work ability, work placement, work motivation and employee competency Keywords: Leadership, Work Environment, Work Effectiveness